2018
DOI: 10.1016/j.jamda.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines for Physicians in Promoting Oral Health in Frail Older Adults

Abstract: Good oral health in old age is particularly important for maintaining adequate oral function, preventing pain and discomfort, controlling localized or systemic inflammation, sustaining social interaction and preserving quality of life. Given that oral health is an integral part of general health and well-being, and that major chronic systemic and oral diseases share common risk factors, oral health prevention and promotion should be embedded within routine medical assessment and care provision. The role of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 61 publications
1
56
0
3
Order By: Relevance
“…Although patients with CKD have been reported to have lower rates of dental visits than the general population [50], regular dental visits and habitual monitoring of oral function, such as the ability to chew, swallow, and eat, are recommended to help prevent severe frailty. Regular check-ups by multidisciplinary medical staff and the establishment of seamless consultations with a dental professional are required [51]. Healthcare providers must perform comprehensive patient management across disciplines and individual specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with CKD have been reported to have lower rates of dental visits than the general population [50], regular dental visits and habitual monitoring of oral function, such as the ability to chew, swallow, and eat, are recommended to help prevent severe frailty. Regular check-ups by multidisciplinary medical staff and the establishment of seamless consultations with a dental professional are required [51]. Healthcare providers must perform comprehensive patient management across disciplines and individual specialties.…”
Section: Discussionmentioning
confidence: 99%
“…A motivated family will seek the resources to provide the best possible care for its loved ones, and there are a lot of good resources as illustrated in the Supporting Information. However, as mentioned above, the physician who diagnosis dementia and the dentist have a very important role in stimulating the patient's families interest in domiciliary oral hygiene care and educating the families about how to provide appropriate daily oral hygiene care . Clinical experience has shown that motivated and educated families can provide excellent care for their loved ones with Alzheimer's disease.…”
Section: Promoting Oral Health Care For Patients With Alzheimermentioning
confidence: 99%
“…However, as mentioned above, the physician who diagnosis dementia and the dentist have a very important role in stimulating the patient's families interest in domiciliary oral hygiene care and educating the families about how to provide appropriate daily oral hygiene care. 64 Clinical experience has shown that motivated and educated families can provide excellent care for their loved ones with Alzheimer's disease. However, there is a moment, usually in the moderate stage of dementia, 36 that behavioral problems become overwhelming for the caregivers and the patients are then referred to a long-term care institution.…”
Section: Establishing and Maintaining Oral Hygiene Routines: Domicilimentioning
confidence: 99%
“…The assessment for removable dentures and teeth in the OHAT are divided into two categories, although those are a same assessment category in the OAG [7,9]. Practical guidelines for physicians describe denture hygiene and maintenance as important for promotion of oral health in frail older adults [27]. That being the case, knowledge of OHAT usage may contribute to the promotion of dental referrals for dentures and oral health for frail inpatients with dentures.…”
Section: Discussionmentioning
confidence: 99%